Electrodeposition of Antimony from Hydrated Ammonium Aluminum Sulfate-Urea Room Temperature Ionic Liquid - Abood, Hadi M. A; Ahmed, Azal U (Al-Nahrain Journal of Science, 2017)
The electrochemical stability of antimony in a water stable room temperature ionic liquid composed of 1:5 mole ratio of hydrated ammonium aluminum sulfate – urea ionic liquid at 30 °C was investigated at 0.3 M antimony (III) chloride solution. The electroplating of antimony at -0.8 V showed black coating on copper substrate. The stability of this cation in this ionic liquid was studied by cyclovoltammogram. The electrodeposition was followed up by Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Energy Dispersive X-ray analysis (EDAX) and X-ray diffraction (XRD).The nanoparticles size of the metal were in the range of less than 500nm.